Study of Maeterlinck's Interior in the Light of Absurdity - Raouf Aminzadeh (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
This article is an attempt to focus on Interior by Maeterlinck in the light of Absurd tradition. Maeterlinck employed symbols to illuminate nature, spirituality, existence, and the innumerable and invisible forces that shape our existence. Maeterlinck uses symbolism to explore the theme of death that is omnipotent in everyday life. The Interior 's central theme is death. Maeterlinck generates suspense by juxtaposing the characters' uneasiness in the garden with the family's peace and ignorance within the house. In order to reach this aim, the researchers decide to explain the theatre of the Absurd and its elements. Maeterlinck distrust of language is shown in his distrust of words, using repetitions, silences, pauses and some other tactics. The existential theme and contents used in selected play are discussed. Themes such as: death, lack of individuality and lack of communication in mentioned play is discussed. Moreover, this article also contains a comparative study of the structure of the two.